The Collapse Analysis of the Lateral-Torsional Buckling of I-Shaped Stepped Steel Beams - Kelsen Trista Kweenisky; Naomi Pratiwi; Paulus Karta Wijaya (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
The use of a non-prismatic member such as a stepped beam as a design method has the ability to function as a tool for steel beams optimization. A cover plate is partially welded on the upper and lower flange of the member at the maximum bending moment location to increase its flexural strength and, under critical load, flexural members bend about its strong axis, displace to the lateral direction, and twist coincidentally through a phenomenon known as the Lateral-Torsional Buckling (LTB). There is, however, no equations in the AISC 360-16 specification to calculate the critical moment of a stepped beam (Mst). Therefore, this research focuses on developing Mst for a simply supported stepped beam which deforms on its shear center under static-transverse loading through the use of a collapse analysis and the behavior of the beam. The results showed the welded cover plates consequently increased the LTB resistance of the prismatic I-shaped steel beam from 9.8% to 202% while the critical moment increased more significantly with an increment in the ratio of the cover plate length to the unbraced length (α). The cover plate thickness was observed to have dominantly affected only a large α ratio while the post-buckling characteristic of large α showed a sudden collapse phenomenon. Furthermore, the LTB modification factor was generated in this study due to the initial geometrical imperfection from the first mode of Eigen shape with maximum amplitude Lb/2000 (Cb1) and stepped beam shape (Cst) which were required to estimate the critical moment of a stepped beam based on the AISC equation for a prismatic beam.